Antibacterial Activity Test of Ethanol Extract of Palm Leaves (Catharantus roseus) Against Staphylococcus aureus and Escherichia coli Bacteria - Fitriana, Yuli; Iradhatullah, Sri Putriani; Sugara, Taufan Hari; Hendriyani, Irmatika; Nurbaety, Baiq; Faisal, Muhammad (THRIVE Health Science Journal, 2025)
Ethanol extract of virgin palm leaves (Catharantus roseus) contains active compounds that have potential as natural antibacterial. This study aims to test the antibacterial activity of the extract against Staphylococcus aureus and Escherichia coli bacteria. The leaves of the tread are extracted using the maceration method with a 70% ethanol solvent. The extraction results showed a yield of 6.1% and the identification of compound content showed the presence of alkaloids, flavonoids, saponins, tannins, and phenols. The antibacterial test was carried out by disc diffusion method using concentrations of 60%, 80%, and 100%. Antibacterial activity was tested by calculating the resulting inhibition zones against both types of bacteria. The results showed that in Staphylococcus aureus bacteria, the concentration of 100% resulted in an inhibition zone of 11.66 mm which was classified as strong. In contrast, in Escherichia coli bacteria, the same concentration resulted in an inhibition zone of 2.66 mm which was in the weak category. This difference in effectiveness is due to the cell wall structure of gram-positive and gram-negative bacteria. The results of this study identified that ethanol extract of virgin leaves has a greater potential for gram-positive bacteria than gram-negative. The ethanol extract of virgin leaves demonstrated antibacterial activity against both Staphylococcus aureus and Escherichia coli, with stronger effects observed against S. aureus.